Viscosities Behavior of CaO-SiO2-MgO-Al2O3 Slag With Low Mass Ratio of CaO to SiO2 and Wide Range of Al2O3 Content - TANG Xu-long ZHANG Zuo-tai GUO Min ZHANG Mei WANG Xi-dong (Journal of iron and steel research, international, 2011)
The present paper is aimed at recycling of coal ash and blast furnace slag to produce mineral wool. Considering the mineralogical constitutions of coal ash and blast furnace slag, the primary quaternary slag compositions of CaO-SiO2-MgO-Al2O3 with basicity （mass ratio of CaO to SiO2 ） ranging from 0.5 to 0.9 and alumina ranging from 5% to 20% were investigated through a rotating cylinder method. The experimental results indicated that the viscosities decreased with increasing basicity above the liquidus temperature, and increased with increasing alumina content, and the maximum values were reached and as the alumina content was 20%, followed by the decrease with further increasing alumina content due to its amphoteric behavior. The amphoteric behavior of Al2O3 also performed in the relationship between viscosity and non-bridging oxygen per tetrahedrally-eoordinated atom （NBO/T）, and the viscosities decreased with increasing the NBO/T except the slag with a basicity 0.5 and Al2O3 20 % which have a low NBO/T value and a low viscosity than others.